2007
DOI: 10.1292/jvms.69.373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pimobendan for Mitral Valve Regurgitation in Dogs

Abstract: ABSTRACT. Pimobendan has a dual mechanism of action: it increases myocardial contractility by increasing calcium sensitization to troponin C and it promotes vasodilation by inhibiting PDEIII. This study examined the effects of pimobendan on cardiac function, hemodynamics, and neurohormonal factors in dogs with mild mitral regurgitation (MR). The dogs were given 0.25 mg/kg of pimobendan orally every 12 hr for 4 weeks. With pimobendan, the heart rate and stroke volume did not change, but the systolic blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 16 publications
4
42
3
1
Order By: Relevance
“…Despite these assumptions and the inodilator properties of PIMO, no significant reduction in the severity of the MR (RV, RF, VTI, and EROA) or significant change in indicators of the severity of the MR (LA/Ao, VHS) were detected in this study. This is contrary to the observations of Kanno et al 6 after introduction of PIMO over a 4‐week period of time in a canine experimental MR model. These investigators actually found a significant reduction of blood pressure, LV diameters, LA : Ao ratio and RV, as well as an increase of FS and EF after introduction of the medication in 4 treated dogs 6 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite these assumptions and the inodilator properties of PIMO, no significant reduction in the severity of the MR (RV, RF, VTI, and EROA) or significant change in indicators of the severity of the MR (LA/Ao, VHS) were detected in this study. This is contrary to the observations of Kanno et al 6 after introduction of PIMO over a 4‐week period of time in a canine experimental MR model. These investigators actually found a significant reduction of blood pressure, LV diameters, LA : Ao ratio and RV, as well as an increase of FS and EF after introduction of the medication in 4 treated dogs 6 .…”
Section: Discussioncontrasting
confidence: 99%
“…This is contrary to the observations of Kanno et al 6 after introduction of PIMO over a 4‐week period of time in a canine experimental MR model. These investigators actually found a significant reduction of blood pressure, LV diameters, LA : Ao ratio and RV, as well as an increase of FS and EF after introduction of the medication in 4 treated dogs 6 . However, no control group was included in this study, and none of the dogs were treated concomitantly with ACEI and PIMO.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There are reports on echocardiographic values of MR dogs after administration of pimobendan . However, there have been few reports evaluating preload after administration of pimobendan.…”
Section: Discussionmentioning
confidence: 96%
“…Pimobendan has increased CO in previous reports . Similarly, in the present study, pimobendan increased CO, but did not affect BP, presumably as a result of the combination of pimobendan's positive inotropic and arterial dilatory effects.…”
Section: Discussionmentioning
confidence: 99%